A comparison between topic signals and strategies in expository essays in English and Arabic / Ienas Ahmed Abdelrahman Fadel - Ienas Ahmed, Abdelrahman Fadel (2014)

(untitled)
This study aims to compare and contrast the use of topic strategies and signals in English and Arabic expository writing using Goutsos’s model of topic organization. The subjects were divided into two groups of students: Native Speakers of English (NSE) and Non-Native Speakers of English (NNSE). The two groups were in secondary schools. The NSE wrote expository compositions in English while the NNSE wrote expository compositions in Arabic and English. The data obtained from the writing samples were analyzed qualitatively and also quantitatively to find out the similarities and differences in the usage of topic strategies and topic signals by native speakers of English and non-native speakers of English in Arabic and English expository essays. The findings of this study showed that the expository writing of both groups of NSE and NNSE exhibit similarities. However; they might differ slightly in the occurrence of certain devices than others. This may be accounted for by the differences of conventions of writing in the two languages as well as some linguistic disparities. The two groups employed the sequential strategies for continuity and discontinuity. They used them to signal the closing of a continuation span, starting a transition span and opening a new continuation span. However, there appear to be some differences in this application (quantity-wise and quality-wise). These differences may be caused by the influence of mother tongue, competence in the language (whether native or non-native), instruction on how to write, ignorance or negligence of the sequential techniques by the students, the teachers or the textbook designers. The study suggested that English teachers should integrate the teaching of reading and writing English and introduce all the topic signals when they are teaching so that students would know and learn the characteristic features of good English writing.